Conformal Conductive Features on Curvilinear Surfaces with Self-Assembled Silver Nanoplate Thin Films - Lai, Yi-Chin; Chiu, Yu-Chieh; Chuang, Kai-Wen; Ramachandran, Balaji; Wu, I-Feng; Liao, Ying-Chih (Langmuir, 2023)
In this study, a water transfer method was developed to fabricate conducive thin-film patterns on 3D curvilinear surfaces. Crystalline silver nanoplates (AgNPLs) with a dimension of 700 nm and a thickness of 35 nm were suspended in ethanol with an anionic surfactant, sodium dodecyl sulfate, to improve the suspension stability. The prepared AgNPL suspension was then spread over the water surface via the Langmuir–Blodgett approach to generate a self-assembled thin film. By dipping an accepting object with a robotic arm, the floating AgNPL thin film with nanometer thickness can be effectively transferred to the object surfaces and exhibited a superior conductivity up to 15% of bulk silver without thermal sintering. Besides good conductivity, the AgNPL conductive thin films can also be transferred efficiently on any curvilinear (concave and convex) surface. Moreover, with the help of masks, conductive patterns can be produced on water surfaces and transferred to curvilinear surfaces for electronic applications. As a proof of concept, several examples were demonstrated to display the capability of this approach for radiofrequency identification and other printed circuit applications.